The efficacy of South African entomopathogenic fungi isolates against immature and mature stages of the Mediterranean fruit fly, Ceratitis capitata - Dlamini, Simphiwe Ntombikhona (Stellenbosch : Stellenbosch University, 2026)
Thesis (MScConsEcol)--Stellenbosch University, 2026.